Practice and associated factors of nurses’ towards patients’ oral care in South Gondar Zone hospitals, Amhara Region, Northwest Ethiopia - Yeshiambaw Eshetie; YohannesTesfahun Kassie; Demewoz Kefale (International Journal of Africa Nursing Sciences)
Introduction: Oral care is a fundamental nursing procedure that has a good impact on a patient’s overall health. Ineffective patients’ oral care has big oral health consequences like oral diseases, difficulty of chewing and swallowing for fluid and diet intakes in general. Although oral health diseases can result in physical, functional, social, emotional, and mental health of the patient, it is given little attention. Objective: The study aims to assess nurses’ patient oral care practice level and its associated factors in South Gondar Zone hospitals, Ethiopia, 2024. Methods: Institution-based cross-sectional study design was used to assess 330 nurses, chosen through convenience sampling technique. Data were collected by using adapted, structured and self-administered questionnaires. The effect of independent variables on the outcome variables was explored by using logistic regression analyses. The levels of significance were determined using an odds ratio with a 95% confidence interval. Results: Of the total 330 study participants, 310 participated with a response rate of 93.9 %. Among the participants, 52.9 % (95 %CI; 47–58) had a good patient oral care practice level. Based on the multivariate analysis, took training (AOR = 1.74; 95 %CI: 1.09, 2.77; p = 0.02) and being female Nurses (AOR = 1.88; 95 %CI: 1.18, 3.00; p = 0.01) were significantly associated with oral care practice of nurses. Conclusions: The finding of this study showed that oral care practice level of nurses was poor. Took training and sex of participants were statistically significant with the nurses’ practice level towards patients’ oral care.